Solution-phase epitaxial growth of platinum nanoparticles on single-layer transition-metal dichalcogenides and their application in hydrogen evolution reaction - Bao, Shuyu (2013)
Hydrogen has been considered to be one of the most promising future energy carriers, and hydrogen powered fuel cells are very efficient energy conservation devices. However, most hydrogen generated from electrochemical process nowadays is catalyzed by platinum (Pt), a precious metal. This report demonstrates a way in developing nonprecious, highly efficient, long life time and acid stable electrocatalysts from transition-metal dichalcogenides (TMD). Three types of Pt/TMD composites (Pt/MoS2, Pt/TiS2 and Pt/TaS2) were synthesized by wet chemical methods (chemical reduction method or photocatalytic reduction method). The size and density of Pt nanoparticles grown on TMD were analyzed with by increasing the growth time. The morphology images and electrochemical properties show that the growth time has significant effect on the morphology, also the distribution of Pt nanoparticles and consequently the electrocatalytic properties of the synthesized materials. Dense growth of Pt nanoparticles with small particle size is favorable in designing highly efficient and stable electrocatalysts. By comparing the hydrogen evolution reaction (HER) results of the synthesized composites with the commercial Pt on activated charcoal, the 2 hr grown Pt/TiS2 composite appeared to be the most promising electrocatalyst among all the synthesized materials. It showed the highest electrocatalytic activity and cyclic stability. It had a current density of −31.39 mA/cm2 at an overpotential of −0.12 V vs. SHE and showed stable cyclability. A relatively small drop in current density was observed after the 1000-cycle cycling test. The enhanced electrochemical properties for TMD based materials provided some new ways in designing highly efficient and cyclic stable Pt/TMD hybrid electrocatalysts and might promote the development in the “hydrogen economy”.